Comparison of Success Rate of Fixed Partial Denture and Root Canal Treatment for the Management of Grossly Carious Teeth - Chechare, Sharmika B; Kumar, O. Pavan; Khandelwal, Ishita; Intern, Debasis Mishra; Sachdeva, Ashwani; Sachdeva, Swati (Journal of Neonatal Surgery, 2025)
Background: This study was conducted to compare the success rate of fixed partial denture and root canal treatment for the management of grossly carious teeth. Material and methods: This study comprised of 100 participants with grossly carious teeth. All the subjects had been informed about the procedure and were asked for consent. All the subjects gave consent for the study and had been included in the trial. The purpose of this study was to compare the success rates of fixed partial denture and root canal treatment for the management of grossly carious teeth. Hence, the subjects had been divided into 2 groups of 50 subjects each. Group 1 consisted of subjects who were planned for fixed partial denture and the 2ng group comprised of 50 subjects who underwent root canal treatment for the management of grossly carious teeth. The findings had been tabulated and statistical analysis was conducted using SPSS software. Results: In this study, there were 50 subjects in group 1 (FPD) and 50 subjects in Group 2 (RCT). When performed RCT, infection was seen in 3 cases, Pain was seen in 2 cases and tooth fracture occurred in 1 case. Total complications were 6/50 (12%). Hence the success rate of RCT was found to be 88%. When given FPD, the complications included denture stomatitis (4/50), debonding and loss of retention (1/50 each) and caries on abutment teeth (2/50). Total complications were 8 (16%). Hence, the success rate of FPD was 84%. Conclusion: Based on the findings of this study, it can be concluded that root canal treatment offers better success rate than fixed partial denture for the management of grossly carious teeth